"I cover the waterfront" - Cruze, James, 1884-1942; Lyon, Ben, 1901-1979; Colbert, Claudette; Miller, Max, 1899-1967.; Reliance Motion Picture Co.; Cinetel Films ([Los Angeles, CA] : [Reliance Pictures Inc.], 1933)
Reporter Joe Miller is sure that fisherman Eli Kirk smuggles illegal Chinese immigrants into the country, but can't obtain enough evidence to satisfy his editor. Chance plays into his hands in the lovely form of Kirk's daughter, Julie, whom he catches swimming in the nude and pumps for information. But she's fiercely loyal to her dad, and may be too attractive for Joe's own good. --
"A Non Theatrical Pictures release."
Originally distributed by United Artists Corp.
Based on the book: I cover the waterfront / Max Miller.
Ben Lyon, Claudette Colbert, Hobart Cavanaugh, Maurice Black, Purnell Pratt, Harry Beresford, Wilfred Lucas.
Cinematographer, Ray June; editor, Grant Whytock.
In English or Spanish.
Keywords: Journalists -- California -- San Diego -- Drama; Waterfronts -- California -- San Diego -- Drama; Human smuggling -- California -- San Diego -- Drama; Illegal aliens -- California -- San Diego -- Drama; San Diego (Calif.) -- Drama; United States -- Emigration and immigration -- Drama; China -- Emigration and immigration -- Drama; United States. -- Coast Guard -- Drama; Thrillers (Motion pictures); Feature films; Film adaptations; Internet videos; Streaming video